Effects of Dual-Task Management and Resistance Training on Gait Performance in Older Individuals: A Randomized Controlled Trial - Wollesen, Bettina; Mattes, Klaus; Schulz, Sören; Bischoff, Laura L.; Seydell, L.; Bell, Jeffrey W.; von Duvillard, Serge P. (Frontiers in Aging Neuroscience, 2017)
Background Dual Task (DT) training is a well-accepted modality for fall prevention in older adults. DT training should include task-managing strategies such as task switching or task prioritization to improve gait performance under DT conditions. Methods We conducted a randomized controlled trial to evaluate a balance and task managing training (BDT group) in gait performance compared to a single task (ST) strength and resistance training and a control group (CG), which received no training. A total of 78 older individuals (72.0 ± 4.9 yrs) participated in this study. The DT group performed task managing training incorporating balance and coordination tasks while the ST group performed resistance training only. Training consisted of 12 weekly sessions, 60 min each, for 12 weeks. We assessed the effects of ST and BDT training on walking performance under ST and DT conditions in independent living elderly adults. ST and DT walking (visual verbal Stroop task) were measured utilizing a treadmill at self-selected walking speed (mean for all groups: 4.4 ±1 km.h-1). Specific gait variables, cognitive performance, and fear of falling were compared between all groups. Results Training improved gait performance for step length (p<0.001) and gait-line (ST: p<0.01; DT p<0.05) in both training groups. The BDT training group showed greater improvements in step length (p<0.001) and gait-line (p<0.01) during DT walking but did not have changes in cognitive performance. Both interventions reduced fear of falling (p< 0.05). Conclusions Implementation of task management strategies into balance and strength training in our population revealed a promising modality to prevent falls in older individuals. Trial registration: German register of clinical trials DRKS00012382